Optimization of Cutting Parameter CNC Wet Milling Process of Austenitic Stainless Steel on Surface Roughness - Hata, Achmad; Widiatmoko, Rudy Yuni; Mulyana, Deni; Azmy, Ilham (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
Austenitic stainless steel (SS) is widely used in various industries owing to its good mechanical properties and corrosion resistance. However, the machineability of this material remains a challenge to measure for better application. In this research, the optimization of the machining parameter CNC wet milling process for austenitic stainless steels (AISI 304 and AISI 316) was successfully finished by utilizing the Taguchi method (S/N ratio and ANOVA) to determine its machineability specifically on surface roughness. The optimum surface roughness of AISI 304 stainless steel is about 0,21 µm within a spindle speed of 3184 rpm, a feed rate of 1528,4 mm/min in the depth of 0,3 mm. The depth of cut parameter during CNC milling was considered as the most influential parameter to optimize surface roughness in AISI 304 stainless steel. Meanwhile, during the cutting process of AISI 316 stainless steel, the optimum surface roughness was obtained at a spindle speed of 3184 rpm, feed rate of 541,4 mm/min in the depth of 0,3 mm with a surface roughness value of 0,24 µm. The results depicted that feed rate held a pivotal factor in determining surface roughness in the AISI 316 stainless steel milling process. Therefore, this research gives impactful insight into developing a good milling process that can increase the machineability, quality, and productivity of AISI 304 and AISI 316 stainless steels.